The health status of Roma women and their participation in prevention programs ZORA and DORA - Zelko, Erika (Anali PAZU, 2022)
This article summarizes the main findings at the research of health of Roma women in Pomurje. The research was part of a controlled interventional studye. The role of women in the Roma community is important and, unfortunately, often too little taken into account when designing health-education activities in the community. Roma women in Prekmurje most commonly reported to have problems with back pain and musculoskeletal diseases (50.6%), followed by depression (31.7%) and chronic obstructive pulmonary disease (28.6%). In the area of ​​reproductive health, we were interested in participation in national prevention programs DORA and ZORA. Younger and more educated Roma women assess more often like very important for their healt the cooperation in the preventive program of early detection of pre-cancerous changes of the cervix (ZORA). 83.4% of Roma women have already participated in the program ZORA. However, we have confirmed that education and age does not have any impact on the need to perform mammography or smear test of the cervix. Mammography have so far carried out 17.5% of Roma women. Younger (p = 0.005) and more educated Roma women (p = 0.016), have statistically typically higher awarnes of the importance of cervical smear test for their health. 94.1% of them have a chosen family doctor, whit hom they are largely satisfied.